Literature Review: Integrasi Etnomatematika Pertanian Dalam Pembelajaran Matematika Sekolah Dasar - Andi Asrafiani Arafah; Suradi Suradi; Rosida Rosida (Mandalika Mathematics and Educations Journal, 2026)
Mathematics learning in elementary schools generally remains abstract and disconnected from students’ real- life experiences, which contributes to low engagement and conceptual understanding. In agricultural-based communities, farming activities hold significant potential as sources of mathematical learning through an ethnomathematical approach. This study aims to explore how agricultural ethnomathematics can be integrated into mathematics learning in elementary schools within a local context. The method used is a Systematic Literature Review (SLR) by examining 12 national and international scholarly articles indexed in Scopus to Sinta 3 from the past seven years. The analysis focused on research objectives, cultural contexts, mathematical concepts developed, and the instructional models applied. The results show that agricultural practices contain mathematical concepts relevant to measurement, geometry, fractions, and ratio topics. However, the implementation of agricultural ethnomathematics remains limited due to teachers’ low cultural- mathematical literacy and the lack of structured teaching materials. This study concludes that integrating agricultural ethnomathematics can improve students’ conceptual understanding and connect learning with their real-life experiences. Therefore, the development of contextual learning modules and instructional models based on local farming practices is recommended for further application.